2009
DOI: 10.1017/s1368980008003169
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of children’s television advertising: focus on food and oral health

Abstract: Objectives: To analyse the nature and content of advertising during children's popular television viewing times with the specific aims of (i) identifying the proportion of advertising time devoted to confectionery and potentially cariogenic products (those which readily give rise to dental caries, more commonly known as tooth decay); and (ii) determining whether there is a variation in the advertisement of confectionery and other high-sugar products within children's school holiday time v. outside holiday time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…Studies in South Africa have reported decreased physical activity among adolescents [45,46]. Increased television viewing by children/adolescents may also be associated with increased consumption of unhealthy foods seen in television advertisements [51]. Length of television viewing by children/adolescents has been associated with higher consumption of fast foods and other high energy dense food and lower intake of fruits and vegetables [52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in South Africa have reported decreased physical activity among adolescents [45,46]. Increased television viewing by children/adolescents may also be associated with increased consumption of unhealthy foods seen in television advertisements [51]. Length of television viewing by children/adolescents has been associated with higher consumption of fast foods and other high energy dense food and lower intake of fruits and vegetables [52].…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries constitute a significant public health problem worldwide (1). Diet, in particular, sugar-rich food, has always been associated with dental caries (2).…”
mentioning
confidence: 99%
“…Food companies sell their products through television advertisement, newspapers, and Internet (3). Marketing methods, such as children’s films, sporting events, film freebies, websites, school books, gifts, on-pack offers, cartoon characters, and film stars, have been used to promote confectionery, high-sugar foods, and junk foods to children (1). …”
mentioning
confidence: 99%
“…television 8,20 . However since the introduction of the 2006 UK Ofcom television regulations 21 companies have been restricted from advertising HFSS foods during children's television viewing times.…”
Section: Advertisingmentioning
confidence: 99%